Optical coherence tomography for longitudinal monitoring of vasculature in scars treated with laser fractionation. Issue 6 (11th August 2015) - Gong, Peijun; Es'haghian, Shaghayegh; Harms, Karl‐Anton; Murray, Alexandra; Rea, Suzanne; Kennedy, Brendan F.; Wood, Fiona M.; Sampson, David D.; McLaughlin, Robert A.
Abstract : This study presents the first in vivo longitudinal assessment of scar vasculature in ablative fractional laser treatment using optical coherence tomography (OCT). A method based on OCT speckle decorrelation was developed to visualize and quantify the scar vasculature over the treatment period. Through reliable co‐location of the imaging field of view across multiple imaging sessions, and compensation for motion artifact, the study was able to track the same scar tissue over a period of several months, and quantify changes in the vasculature area density. The results show incidences of occlusion of individual vessels 3 days after the first treatment. The subsequent responses ˜20 weeks after the initial treatment show differences between immature and mature scars. Image analysis showed a distinct decrease (25 ± 13%, mean ± standard deviation) and increase (19 ± 5%) of vasculature area density for the immature and mature scars, respectively. This study establishes the feasibility of OCT imaging for quantitative longitudinal monitoring of vasculature in scar treatment.En face optical coherence tomography vasculature images pre‐treatment (top) and ˜20 weeks after the first laser treatment (bottom) of a mature burn scar. Arrows mark the same vessel pattern. Abstract : This study uses optical coherence tomography to longitudinally quantify vascular changes in human burn scars over a period of months. We identify changes in scars due to the use of ablative fractional laser treatment. A series of case studies demonstrate the feasibility of OCT for longitudinal assessment of vasculature in burn scars and provide novel insight into the acute and long‐term vascular responses to treatment in immature and mature scars.